How the histamine N-methyltransferase inhibitor metoprine alleviates methamphetamine reward - Nobue Kitanaka; Junichi Kitanaka; F Scott Hall; Satoshi Okumura#; Tomoyuki Sakamoto#; George R Uhl; Motohiko Takemura (Journal of Addiction Medicine and Therapeutic Science - Peertechz Publications, 2017)
Methamphetamine (METH) is a highly addictive psychomotor stimulant drug that is abused worldwide [1]. METH abuse results in numerous adverse effects after acute administration, as well as an array of adverse outcomes associated with binge use, long-term use, and withdrawal [2- 4]. Acutely METH releases dopamine from synaptic terminals through multiple actions that include inducing reverse transport of dopamine via the dopamine transporter (DAT), impairing the function of the vesicular monoamine transporter-2 (VMAT2), leading to increased cytoplasmic dopamine concentrations, and inhibition of monoamine oxidase [5-8]. Moreover, these changes contribute to the production of oxidative metabolites, metabolic impairments, oxidative damage to dopamine terminals, and depletion of tissue dopamine levels [9-11]. METH and related drugs consequently produce broad effects on the central nervous system both acutely and chronically [12-14].